Implication of some pre-germination treatments on seeds and initial seedling growth of pomegranate (Punica granatum L.) - Monteiro, Laís Naiara Honorato [UNESP]; Boliani, Aparecida Conceição [UNESP]; Ferreira, Antonio Flávio Arruda [UNESP]; Rodrigues, Maria Gabriela Fontanetti [UNESP]; Faria, Gláucia Amorim [UNESP]; da Silva, Marcela Sant'anna Cordeiro; Oliveira, Marcela Pacola; Cunha, Silvia Regina [UNESP]; Ribeiro, Luiza Rocha [UNESP] (Southern Cross Publishing, 2019)
Pomegranate stands out as healthy fruit due to its phytochemical compounds. Some dormancy studies have stated the need to understand seed physiology, subsequent seedling production, as producers intended to expand the supply of pomegranate, besides facilitating the introduction of such promising crop. Thus, this study aimed to identify possible integumentary dormancy in seeds of pomegranate cultivar Comum and to evaluate the effect of mechanical scarification and water immersion of seeds, as overcoming method. In this study, sarcotesta was removed from scarified and non-scarified seeds, and then immersed in deionised water for up to 0, 12, 24 and 48 hours. Then seeds were embedded in trays of expanded polystyrene with organic substrate at greenhouse. The following evaluations were carried out: initial emergence, speed index, mean time of emergence and emergence percentage, besides biometric variables such as leaf number, stem diameter, length of aerial part and root system, fresh matter and total dry matter. A 2 × 4 factorial arrangement (presence or absence of scarification × four immersion time) in a completely randomized design was used, with 4 replicates of 25 seeds each. The results showed that seeds do not need to be scarified and immersed in water, regarding to both emergence and initial seedling growth variables. Results indicated that it was unnecessary to perform scarification and water immersion for emergence and initial growth variables, leading to conclusion that pomegranate seeds cv. Comum have no integumentary dormancy.
Keywords: Dormancy; Pomegranate; Rootstock; Sarcotesta; Scarification